Analysis on Customer Satisfaction Dimensions in P2P Accommodation using LDA: A Case Study of Airbnb - Kevin Situmorang; Achmad Hidayanto; Alfan Wicaksono; Arlisa Yuliawati (IAES Indonesia Section, 2018)
Customer satisfaction becomes a key influencer for people's habits or daily activities. One of the examples is in the decision-making process about whether they will use specific products or services. People often need other's review or rating about what they are going to use or consume. In this research, by using customer's online review that available from Airbnb website, we try to extract what are the most talked factors about peer-to-peer accommodation, and how customer sentiment about them. We use Latent Dirichlet Allocation (LDA) to extract that factors and conduct sentiment analysis by utilizing semantic analyzer from Google Cloud NLP. We analyze which factors that has more effect on customer satisfaction, not only in general but more specific based on customer gender and tourism destination object. The result shows that factors related to social benefit and service quality have impact on customer satisfaction, moreover different customer gender and different tourism object destination bring different sentiment among customer. We also find several factors that can be improved by the owner of the accommodation to improve customer satisfaction toward their services.